Institutions, norms and monasticism in Lion and Castile (13th century) - Coelho, Maria Filomena (2013)
This article intends to explain the monastic enclosure in a political culture perspective that embodied the cistercian rules, mainly the feminine branch, in Lion and Castile in the 13th century. As part of the problem will be necessary to analyze how the nuns were institutionalized, in the masculine perspective of the Cistercian order, specially the difficulties faced by the traditional historiography to deal with the matter. The tensions and conflicts registered on the documents that involved the observance to enclosure, the juridical recognition of the monasteries, or the jurisdictional bounds, must be explained in the political context of each kingdom or region, without forgetting the political and social nets where those actors belonged.